Convergent Evolution of Broadband Reflectors Underlies Metallic Coloration in Butterflies - Ren, Anna; Day, Christopher R.; Hanly, Joseph J.; Counterman, Brian A.; Morehouse, Nathan I.; Martin, Arnaud (Frontiers in Ecology and Evolution, 2020)
Butterfly wings often display structural colors, which are the result of light reflection from chitinous nanostructures that adorn the wing scales. Amongst these structural colors are broadband metallic reflections, which have been previously linked to an ultrathin broadband reflector in the nymphalid butterfly Argyrophorus argenteus. To test if similar optical modes of broadband, specular reflectance have evolved in other butterfly taxa, we characterized the reflective scales of eight species from five Papilionoidea families using microspectrophotometry (MSP), light microscopy in reflected and transmitted modes, and scanning electron microscopy (SEM). In Nymphalidae, Pieridae, and Hesperidae, and Lycaenidae, we find that broadband specularity is due to spatial mixing of densely juxtaposed colorful reflectances that change across microscale distances (e.g. 1-3 µm). These seemingly convergent silver scales are unpigmented, show a continuous upper lamina with reduced windows, and consist of an air-cuticle sandwich of variable thickness, forming an undulatory thin-film. Strikingly, Hypochrysops apelles (Lycaenidae) show a novel mode of silver reflectance with spatial color mixing occurring across the entire proximo-distal length of the scale (>100 µm), transitioning from blue to red hues between the stem and the tip of the scales. Unlike the undulatory type, this reflector shows flat thin-films but this includes a multilayered lower lamina responsible for selective color iridescence in other lycaenids or in sunset moths. Finally, the gold scales of Anteros formosus (Riodinidae) show mixed reflectance in the green-to-red range, seemingly produced by a thin film in the lower lamina. Our comparative study suggests that evolution of metallic broadband reflectance repeatedly involved spatial color mixing and unperforated upper laminae, and is accomplished using at least three types of ultrastructural modifications. Undulatory thin-film systems, based on geometric adjustments of the transverse profile of the upper lamina and scale lumen, are widespread and may have evolved repeatedly from more generic colorless scale morphologies, while lycaenid and riodinid broadband reflectors may be elaborations of pre-existing iridescent states.